ANALISIS PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN PRODUKSI DI PT EXCELITAS TECHNOLOGIES BATAM - Jumarni; Sri Zetli (LPPM Universitas Putera Batam, 2024)
ABSTRACT Employee workloads vary depending on their specialized fields. For example, in the production area, workers are required to work swiftly due to the constant operation of production machinery. Certain positions, like the Hercules section operator assisting with the depanelizing process, are not appropriate for people in those professions. Support staff members have to put in extra hours because of the incoming and unloaded items. There are challenges due to data mistakes, the human calculating method, and the manual lifting of 5–10 kg objects. At PT Excelitas Technologies Batam, the goals of this research were to ascertain the effects of workload and work stress on manufacturing employee performance, as well as the results of measuring workload utilizing the NASA-TLX technique and measuring work stress using the Health and Safety Executive (HSE) technique. Using the technique of multiple linear regression, the HSE method, and the NASA-TLX approach, the study methodology is quantitative. The High mental load group's average score was 70.20 according to the data. Mental Needs is the most prominent measure of mental workload, with an average score of 5509.87. The average result of the job stress measurement was 142.3 and 81.31%. Employee performance is negatively but negligibly impacted by workload. Employee performance is negatively and significantly impacted by work stress. At PT Excelitas Technologies Batam, the performance of production staff is negatively impacted by workload and work stress.